The RNA-binding protein, HuD regulates proglucagon biosynthesis in pancreatic α cells - Ahn, Sojin; Tak, Hyosun; Kang, Hoin; Ryu, Seungyeon; Jeong, Seung Min; Kim, Wook; Lee, Eun Kyung (Biochemical and Biophysical Research Communications, 2020)
Glucagon is a peptide hormone generated by pancreatic α cells. It is the counterpart of insulin and plays an essential role in the regulation of blood glucose level. Therefore, a tight regulation of glucagon levels is pivotal to maintain homeostasis of blood glucose. However, little is known about the mechanisms regulating glucagon biosynthesis. In this study, we demonstrate that the RNA-binding protein HuD regulates glucagon expression in pancreatic α cells. HuD was found in α cells from mouse pancreatic islet and mouse glucagonoma αTC1 cell line. Ribonucleoprotein immunoprecipitation analysis, followed by RT-qPCR showed the association of HuD with glucagon mRNA. Knockdown of HuD resulted in a reduction in both proglucagon expression and cellular glucagon level by decreasing its de novo synthesis. Reporter analysis using the EGFP reporter containing 3′ untranslated region (3′UTR) of glucagon mRNA showed that HuD regulates proglucagon expression via its 3′UTR. In addition, the relative level of glucagon in the islets and plasma was lower in HuD knockout (KO) mice compared to age-matched control mice. Taken together, these results suggest that HuD is a novel factor regulating the biosynthesis of proglucagon in pancreatic α cells.
Keywords: Animals; Biosynthetic Pathways; Cell Line; Cell Line, Tumor; Down-Regulation; ELAV-Like Protein 4; Gene Knockdown Techniques; Glucagon-Secreting Cells; Mice; Proglucagon; RNA, Messenger; Alpha cell; Glucagon; HuD; RNA binding Protein